Is the P/E ratio good predictor of Stock Return in Saudi Stock Market both in long and short term? - Al-Rashoud, Abdullah (2005)
Since a long time ago, people were looking for opportunities in the market where they can make profits with lower risk or similar risk but with excess return. Stocks with low price earnings (P/E) ratio is claimed to be one of those opportunities. The Saudi stock market is an emerging market with low efficiency. This dissertation is supposed to find out whether the P/E ratio is a good predictor of Stock Return in Saudi Stock Market both in long and short term.